2020
DOI: 10.1111/jfbc.13548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zanthoxylum alkylamides on lipid metabolism and its mechanism in rats fed with a high‐fat diet

Abstract: This research aimed at exploring the effect of Zanthoxylum alkylamides on lipid metabolism and its potential mechanisms using high-fat diet rat model. Treatment with Zanthoxylum alkylamides for 6 weeks, food efficiency and atherogenic index of the low, medium, and high doses of Zanthoxylum alkylamides-treated groups were significantly reduced. Meanwhile, the histopathological structure of the livers showed that hepatic steatosis in the groups treated with Zanthoxylum alkylamides was reduced, particularly the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In medicine, hyperlipidaemia is often attributed to abnormal lipid operation and metabolism, manifesting increased serum TC, TG and LDLC contents and reduced HDLC content (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In medicine, hyperlipidaemia is often attributed to abnormal lipid operation and metabolism, manifesting increased serum TC, TG and LDLC contents and reduced HDLC content (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By activating TRPV1 channels, they cause an increase in intracellular free Ca 2+ levels, thus triggering the desensitization of nociceptive neurons [ 82 ] and the suppression of visceral fat accumulation through the upregulation of UCP1 (Mitochondrial Uncoupling Protein 1) [ 83 ]. Lipid metabolism has also been found to be regulated by the interaction of TRPV1 with transcription factors involved in energy homeostasis, such as peroxisome proliferation-activated receptors (PPARs, [ 84 , 85 ]) and sterol-responsive element-binding proteins (SREBPs, [ 86 , 87 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies concluded that overexpression of TRPV1 is involved in the pathogenesis of metabolic diseases. In contrast, low expression of TRPV1 has been reported to be involved in metabolic syndrome (Baskaran et al, 2016;Krishnan et al, 2019;Wang et al, 2020). In apolipoprotein E-deficient mice, evodiamine significantly reduced atherosclerosis, hyperlipidemia, and systemic inflammation and this beneficially therapeutic effect was not seen in ApoE −/− mice that lack TRPV1 (Wei et al, 2013), suggesting that TRPV1 curbs the development of atherosclerosis.…”
Section: Trpv1 Expression Is Suppressed In Metabolic Syndromementioning
confidence: 99%
“…Tart cherry supplements downregulated the HFD-induced expression of adipogenesis-related genes including SREBP-1c accompanied by down regulation of TRPV1 ( Cocci et al, 2021 ). Similarly, zanthoxylum alkylamides ameliorated abnormal lipid metabolism in rats fed HFD through upregulation of TRPV1 and downregulation of SREBP-1c ( Wang et al, 2020 ). It seems that the lipid lowering effect exerted by these plants products is attributed to modulation of TRPV1 that may be involved in the down regulation of SREBP-1c.…”
Section: Potential Molecular Mechanisms Underlying Trpv1 Regulation O...mentioning
confidence: 99%